ON THE ROAD TO LEGITIMATION OF JURIDICAL LOGIC - Тягло, А. В. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2016)
Issues of existence and specificity of juridical logic are analyzed from different sides in this paper. It is argued, that juridical logic exists, firstly, in re – as special order of correct reasoning in field of law stable in some temporal or cultural frames; secondly, post rem – as a part of nowadays science of logic, directly «semi-formal», which studies the special order and teaches by what way to implement this one, i. e. deliberatively construct legally correct reasoning, avoid or criticize fallacies. Adoption of values of human being and law in today civilized world generates some norms of correctness of juridical reasoning, which differ from norms of the traditional formal logic coherent to the «mathematical model».